Understanding evidence use from a programmatic perspective: conceptual development and empirical insights from national malaria control programmes. (1st August 2021) - Parkhurst, Justin; Ghilardi, Ludovica; Webster, Jayne; Hoyt, Jenna; Hill, Jenny; Lynch, Caroline A.
Abstract : Background: Conceptualisations of what it means to use evidence in policymaking often appear divided between two extremes. On the one side are works presenting it as the implementation of research findings ‐ particularly evaluations of intervention effect. In contrast stand theoretically informed works exploring the multiple meanings of evidence use, political complexities, and the constructed nature of research evidence itself. The first perspective has been criticised as over-simplistic, while the latter can make it difficult to answer questions of what might be good, or improved, uses of evidence in policymaking.Methods: To further debate, this paper develops a 'programmatic approach' to evidence use, drawing on theories of institutional decision making and empirical work on evidence use within 11 National Malaria Control Programmes in Africa. We apply the programmatic approach by investigating the key goals and tasks of programme officials, recognising that these will shape the routines and logics followed affecting evidence utilisation. We then map out the forms, sources, features, and applications of evidence that serve programme officials in their goals.Findings: In the case of malaria programmes, evidence use was understood in relation to tasks including: advocacy for funding, budget allocation, regulation development, national planning, and identification of information gaps ‐ all of which might require different evidence sources, forms, and applications.Discussion and conclusions: Ultimately the programmatic approach aims to facilitate clearer understanding of what uses of evidence are appropriate to policymakers, while also allowing critical reflection on whether such uses are 'good' from both programme and broader social perspectives.